Cantonese Tone Identification in Three Temporal Cues in Quiet, Speech-Shaped Noise and Two-Talker Babble - Wong, Puisan; Cheng, Sheung Ting; Chen, Fei (Frontiers in Psychology, 2018)
Purpose. Cochlear implant processors deliver mostly temporal envelope information and limited fundamental frequency (F0) information to the users, which make pitch and lexical tone perception challenging for cochlear implantees. Different factors have been found to affect Mandarin tone perception in temporal cues but the most effective temporal cues for lexical tone identification across different backgrounds remained unclear because no study has comprehensively examined the effects and interactions of these factors, particularly, in languages that use both pitch heights and pitch shapes to differentiate lexical meanings. The present study compared identification of Cantonese tones in naturally produced stimuli, and in three temporal cues, namely the amplitude contour cue (TE50), the periodicity cue (TE500), and the temporal fine structure cue (TFS), in three different numbers of frequency bands (B04, B08, B16) in quiet and two types of noise (two male talker-babble and speech-shaped noise). Method. Naturally produced Cantonese tones and synthetic tones that combined different acoustic cues and different number of frequency bands were presented to eighteen young native Cantonese speakers for tone identification in quiet and noise. Results. Among the three temporal cues, TFS was the most effective for Cantonese tone identification in quiet and noise, except for T4 (LF) identification. Its effect was even stronger when the tones were presented in 4 or 8 bands rather than 16 bands. Neither TE500 nor TE50 was effective for Cantonese tone identification in quiet or noise. In noise, most tones in TE500 and TE50 were misheard as T4 (LF), demonstrating errors in both tone shapes and tone heights. Types of noise had limited effect on tone identification. Conclusions. Findings on Mandarin tone perception in temporal cues may not be applicable to other tone languages with more complex tonal systems. TFS presented in four bands was the most effective temporal cue for Cantonese tone identification in quiet and noise. Temporal envelope cues were not effective for tone, tone shape or tone height identification in Cantonese. These findings have implications for future design of cochlear implants for tone speakers who use pitch heights or a combination of pitch heights and pitch shapes to differentiate meanings.